Drake, Videll (audio interview #1 of 3) - Drake, Videll (b. 1/11/1912 - d. 7/25/1995); Fischer, Jan, interviewer
INTERVIEW DESCRIPTION - This is the first of three interviews with Videll Drake conducted at a small table in the dining area of her one story home in South Central Los Angeles. Because Drake has a tendency to talk about subjects without providing sufficient background, it is a bit difficult to develop a clear understanding of her life. 9/8/1980